Bandwidth Control in Computer- Generated Holography - Mian Wu; Lin Wu; Ying Qiu; Chao Yang; Zhixue He; Jin Tao; Xi Xiao (IEEE Photonics Journal, 2023)
The Fourier transform between the time and frequency signals of light enables highly efficient band usage in optical communications. Analogously, the Fourier transform between the wavefield and wavevector distributions in the optical spatial diffraction is useful to understand the bandwidth considered in the diffraction simulations. In this work, we thoroughly investigate the numerical techniques for controlling the bandwidth in the design of computer-generated holography. The experiments reveal the effects of bandwidth control on both accuracy improvement of diffraction equations and suppression of higher hologram orders. A general formula for controlling the bandwidth directly using the spatial-frequency components is concluded.